Treatment access gap during the COVID-19 Pandemic: impact on problematic alcohol use and the moderating roles of perceived stress and resilience - Vergeer, Rhianna R.; Luk, Jeremy W.; Stangl, Bethany L.; McCabe, Emma M.; Ziausyte, Ugne; Schwandt, Melanie L.; Goldman, David; Ramchandani, Vijay A.; Diazgranados, Nancy (Frontiers in Psychiatry, 2024)
ObjectiveThe COVID-19 pandemic may have interfered with individuals’ access to alcohol use disorder (AUD) treatment, but limited research has documented the impact of treatment interference on drinking behavior. This study’s purpose was to examine the associations of AUD treatment interference with problematic alcohol use, and the moderating roles of perceived stress and resilience.MethodA cross-sectional survey design was employed. Data were drawn from the baseline assessment of the National Institute on Alcohol Abuse and Alcoholism COVID-19 Pandemic Impact on Alcohol Study. Between June 2020 and March 2021, 288 participants (48.6% female, 51.4% male) responded to key measures of interest by phone and/or through an online survey. Study hypotheses were tested using multiple linear regression models adjusted for demographic characteristics (age, sex, race, ethnicity, years of education, household income, marital status), study enrollment phase, and history of AUD.ResultsSelf-reported AUD treatment interference was positively associated with problematic alcohol use as measured by the Alcohol Use Disorders Identification Test (b = 2.05, p < 0.001). Significant moderation effects indicated the association between AUD treatment interference and problematic alcohol use was stronger at a high level of perceived stress (b = 3.08, p < 0.001) and was attenuated at a high level of resilience (b = -0.13, p = 0.874).ConclusionsSelf-reported AUD treatment interference may indicate interruption to individuals’ support systems and highlight the need for continued access to treatment. Fostering positive coping strategies and resilience may help individuals mitigate risks of problematic drinking amidst a public health crisis.